Effect of Different Composite Restorations on the Cuspal Deflection of Premolars Restored with Different Insertion Techniques- An In vitro Study - SAKSHI SINGHAL (Journal of Clinical and Diagnostic Research, 2017)
Introduction: This study was conducted to assess the effect of different composite materials on the cuspal deflection of premolars restored with bulk placement of resin composite in comparison to horizontal incremental placement and modified tangential incremental placement. Aim: The aim of this study was to evaluate the cuspal deflection caused by different composite materials when different insertion techniques were used. Materials and Methods: Two different composite materials were used that is Tetric N Ceram (Ivoclar Vivadent marketing, India) and SonicFillTM (Kerr Sybron Dental). Forty standardized Mesio-Occluso-Distal (MOD) preparations were prepared on maxillary first premolars. Each group was divided according to composite insertion technique (n=10), as follows: Group I – bulk insertion using Tetric N Ceram, Group II - Horizontal incremental insertion technique using Tetric N Ceram, Group III- Modified tangential incremental technique using Tetric N Ceram, and Group IV- bulk insertion using SonicFillTM. Preparations were acid-etched, and bonded with adhesive resin to provide micro mechanical attachment before restoration using a uniform etching and bonding protocol in all the groups. All groups received the same total photo-polymerization time. Cuspal deflection was measured during the restorative procedure using customized digital micrometer assembly. One-way ANOVA test was applied for the analysis of significant difference between the groups, p-value less than 0.05 was considered statistically significant. Results: The average cuspal deflections for the different groups were as follows: Group I 0.045±0.018, Group II 0.029±0.009, Group III 0.018±0.005 and Group IV 0.017±0.004. The intergroup comparison revealed statistically significant difference. Conclusion: A measurable amount of cuspal deflection was present in all the four studied groups. In general, bulkfill restoration technique with conventional composite showed significantly highest cusp deflection. There were no significant differences in cuspal deflection among sonicFillTM and modified tangential incremental insertion techniques.